Emotional Control is Predicted by Brain Reward Processing in Athletes with Previous Concussions. (26th July 2019) - Agate, F T; Wong, R E; Gordon, I; Webster, L; Karr, J; Garcia-Barrera, M A
Abstract: Purpose: Limited research examines how electrophysiological markers of reward sensitivity in athletes with concussion history may relate to corresponding executive behavior. Therefore, the present study aimed to examine the relationship between event-related brain potentials (ERPs) elicited during a reward-processing task, and self-report of emotional control and initiation problems in athletes with and without a history of concussion. Methods: A total of 38 collegiate athletes (53% females, ages 18-27 years) completed a reward task in a "virtual T-maze" environment, as well as the BRIEF-A. The reward positivity (RewP), an ERP component associated with reward processing, was regressed on endorsement of emotional control and initiation problems in athletes with a history of concussion (n=16) and in athletes with no concussion history (n=22). Results: A multiple regression analysis showed that in the concussion group, RewP peak amplitude explained a significant proportion of variance in emotional control, r 2 =.36, F(1, 13)=6.76, p=.02, but did not for initiation, r 2 =.05, F(1, 13)=.60, p>.05. For athletes with no history of concussion, RewP peak amplitude did not explain a significant proportion of variance in either emotional control, r 2 =.003, F(1, 21)=.05, p>.05, or initiation, r 2 =.11, F(1, 21)=2.49, p=.13. Conclusion: Results indicate that for athletes with a history of concussion, a lower electrophysiological response to reward may predict greater problems concerning emotional control. Potential implications are discussed for how decision-making, an integral cognitive process driven by reward processing, might impact emotional regulation following concussion.